Adult plant resistance in some Indian wheat cultivars and postulation of yellow rust resistance genes - and J. KUMAR, SUBODH KUMAR*, R.P. AWASTHI (Indian Phytopathology, 2014)
Old wheat varieties were screened against different pathotypes of Puccinia striiformis for yellow rust resistance both at seedling in temperature controlled green house as well as adult plant stage under field conditions. By applying the gene matching technique, different combinations of three yellow rust resistance genes, viz. Yr2, Yr9 and Yr18 were characterized. Promising adult plant resistance was observed on the varieties GW173, HUW234, HW741, K8027, K9006, K9107, NIAW34, Raj3765, SKW196, VL404, VL616 and WH542 consistently during cropping season 2010-11 and 2011-12.